The Role of Saving in a Growth Model with Induced Inventions: A Correction - Burmeister, Edwin; Chang, Winston W.; Dobell, Rodney (The Review of Economics and Statistics, 1970)
Edwin Burmeister, Winston W. Chang, Rodney Dobell, The Role of Saving in a Growth Model with Induced Inventions: A Correction, The Review of Economics and Statistics, Vol. 52, No. 4 (Nov., 1970), pp. 446-447